PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN BEKAS (THRIFTING): STUDI KASUS PADA KONSUMEN MISSMI SHOP DI KOTA PALANGKA RAYA - Melda Oktavia, Sri; Nahan, Noorjaya; Harjoni, Harjoni; Sukmani, Meylinda (Penerbit Lafadz Jaya, 2026)
This study analyzes the effect of price and promotion on purchasing decisions for secondhand clothing (thrifting) among Missmi Shop consumers in Palangka Raya City. Using a quantitative method with multiple linear regression analysis on 96 respondents through purposive sampling. Data were collected using online questionnaires and analyzed with SPSS Version 27. The results show that partially price has no significant effect on purchasing decisions, while promotion has a positive and significant effect. Simultaneously, both variables have a significant effect with a good ability to explain variations in purchasing decisions. The study concludes that promotion is the dominant factor in driving thrift purchasing decisions, while price is not the main consideration for consumers. Future research is recommended to add variables such as product quality, brand image, and shopping experience, as well as expand the diversity of respondents.